Dynamically consistent intertemporal dual-self expected utility - Lasse Mononen (Bielefeld University, Center for Mathematical Economics (IMW), 2024)
Experimental evidence on intertemporal choice has documented a preference for consumption smoothing that cannot be explained by discounted utility. We study a general class of dynamically consistent intertemporal dual-self preferences that accommodate a preference for consumption smoothing. We show that these general preferences have a simple and tractable structure. They are characterized by a gain-loss asymmetry where gains with respect to future utility are discounted differently than losses. As applications, first, we show that under the stationarity axiom, these preferences are convex or concave. Second, we show that dynamically consistent intertemporal Choquet expected utility coincides with discounted expected utility.
urn:nbn:de:0070-pub-29872861
Keywords: 330